2014
DOI: 10.1021/la502802f
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Characteristics and Determination of Cohesive and Adhesive Strength of Plasma-Coated Hydroxyapatite via Nanoindentation and Microscratch Techniques

Abstract: We investigate the chemical composition and mechanical properties of plasma-deposited hydroxyapatite on grit-blasted Ti-6Al-4V coupons as models of typical prosthetic hip implants. Nanoindentation is used to extract the mechanical properties of the hydroxyapatite (HA) coating and to evaluate the behavior of the material as a function of distance from the interface. A microscratch technique was used to determine parameters of cohesive and adhesive failure of the material that are critical in determining the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…On the other hand, some other studies reported much lower E and H values. For instance, McManamon et al [22] found that their plasma sprayed HA coatings possessed a E of 4.1 GPa and a H of 0.29 GPa; low E (6 GPa) and H (1 GPa) were also obtained by Sidane et al [23] for their sol-gel HA coating, although they used the same indentation depth and strain rate as our study. These results suggest that the mechanical properties of HA coatings depend on various factors such as crystallinity, porosity, particle size and processing routes.…”
Section: Coating Propertiessupporting
confidence: 64%
“…On the other hand, some other studies reported much lower E and H values. For instance, McManamon et al [22] found that their plasma sprayed HA coatings possessed a E of 4.1 GPa and a H of 0.29 GPa; low E (6 GPa) and H (1 GPa) were also obtained by Sidane et al [23] for their sol-gel HA coating, although they used the same indentation depth and strain rate as our study. These results suggest that the mechanical properties of HA coatings depend on various factors such as crystallinity, porosity, particle size and processing routes.…”
Section: Coating Propertiessupporting
confidence: 64%
“…28. Furthermore, fatigue [148,774], scratch [744,749,[775][776][777][778][779] and pullout [775] testing, as well as wear resistance [777] are among the most valuable techniques to provide additional information on the mechanical behavior of CaPO 4 deposits. The scratch test is performed with reference to ISO 20502:2005 [780].…”
Section: Adhesion and Cohesionmentioning
confidence: 99%
“…The primary and most basic property is to achieve high bonding strength in the interface between the coating material and metal substratum. Due to hydroxyapatite's (HA) close similarity with the predominant inorganic component of bone, HA coatings have been widely applied to modify the metal substratum [8,9], resulting in high cytocompatibility and osteogenic effects. Implants modified this way have been shown to integrate better with the host bone tissue, leading to a higher success rate of implantations.…”
Section: Introductionmentioning
confidence: 99%